Phylogeography of the magpie-robin species complex (Aves: Turdidae: Copsychus) reveals a Philippine species, an interesting isolating barrier and unusual dispersal patterns in the Indian Ocean and Southeast Asia - Sheldon, F.H. (2014)
10.1111/j.1365-2699.2009.02087.x